INTRAPERSONAL FACTORS AFFECTING THE SUBJECTIVE WELL-BEING OF STUDENT YOUTH - Olga YAKOVENKO; Anastasiia TESLENKO (Association of Social and Educational Innovation, 2024)
The article explores various approaches to understanding the concept of subjective well-being and examines the factors that contribute to achieving a state of well-being. It also discusses the relationship between intrapersonal resources and human traits such as resilience, worldview, self-control, and meaning, and how they impact life satisfaction. Lastly, the article provides methodological recommendations for enhancing the level of subjective well-being by tapping into students' internal resources.